Community empowerment with the making of liquid organic fertilizer from banana slim stem - Nensi Ulfatun Khasanan; Hari Sutrisno (Peneliti Teknologi Teknik Indonesia, 2021)
Banana is a plant that is not foreign to the community. Banana (Musa Pradisianca) comes from Asia and spreads in Spain, Italy, Indonesia and America. Banana plants can be used in liquid organic fertilizers, fertilizers are materials that are added to the soil to provide essential elements for plant growth. When viewed based on the source of the material used, fertilizers are divided into inorganic fertilizers and organic fertilizers. The banana plant is a plant that only bears fruit once in its lifetime and after that the banana tree will not bear fruit again. After that the tree will be left to die and even just left alone. In the stem of the banana midrib there are important elements needed by plants, the content of nutrients contained in the banana midrib, namely N (nitrogen), P (phosphorus), and K (potassium). The results of the implementation of the Banana Stem Liquid Organic Fertilizer Manufacturing program in Guyangan Village, Loano, Purworejo, Central Java, went smoothly. This program is considered very useful for the people of Guyangan Village in order to reduce environmental problems in the form of banana stem waste and improve the people's economy by utilizing useless banana stem waste into something that can be reused.